Rare Presentation of Chorioadenoma Destruens as Acute Haemoperitoneum Mimicking Ruptured Ectopic Pregnancy - Sinha, M; Kaur, R; Gupta, R; Rani, R; Aggarwal, A (Kathmandu University Medical Journal, 2015)
Gestational trophoblastic neoplasms (GTN) are proliferative degenerative disorders of placental elements and include complete or partial mole (90%), invasivemole (5-8%), choriocarcinoma (1-2%) and placental site tumor (1-2%). Chorioadenoma destruens is a trophoblastic tumor, characterized by myometrial invasion through direct extension or via venous channels. We present a case of invasive mole eroding uterus and uterine vasculature, causing sudden rupture of uterus with massive haemoperitoneum mimicking ectopic pregnancy. A 20 year old G1P0 at 6 weeks gestation presented in Casualty of Kasturba Hospital complaining of severe acute onset lower abdominal pain for one hour. Clinical examination revealed shock. Sonography suggested ectopic pregnancy and immediate exploratory laparotomy was decided. On laparotomy, 2000cc of haemoperitoneum was noted. Grape like vesicles protruding through fundal perforation with profuse active bleeding was seen. Bleeding persisted despite evacuation. Step wise uterine devascularisation failed to achieve haemostasis. Total abdominal hysterectomy was performed as a life saving measure.Kathmandu University Medical Journal Vol.12(4) 2014; 288-291